A LOCAL EXAMPLE OF THE IMPACT OF CIVIL SOCIETY ORGANIZATIONS ON CHANGE IN GOVERNANCE: YUNUS EMRE CULTURAL FOUNDATION (KARAMAN) - AKAY, Hasan (SSD Journal, 2022)
The individual, who constitutes a part of social life, is in cooperation with other individuals to achieve common goals as well as substituting his life. The concept of management is also generally manifested in these mentioned environments. The change in the goals or perceptions of individuals will naturally affect the management phenomenon articulated with the social lives of individuals. Since the direct addressee of the concept of management, which is among the disciplines of social life, is the individual, all the change and development related to the individual can be associated with the concept of management. Non-governmental organizations are among the most important structures where individuals come together with purpose or unity of mind within the social life bloc. Non-governmental organizations are able to influence the individuals they host within their bodies and have the power to change the perception of concepts in their minds and various balances of life. The individual who will experience a change of mind will now interpret life according to his new perception and will desire this change in the main themes he constantly encounters. The aim of this study is to discuss whether non-governmental organizations have an impact on the changes in many areas from bureaucratic understanding to service understanding in management. In this context, the effects of the Yunus Emre Cultural Foundation, which is a local actor in Karaman, on the change in management approach, whether it uses them as a pressure factor or whether it carries out them with a non-governmental organization reflex according to the feedback from the society were examined. As a result, the study showed that the Yunus Emre Cultural Foundation as a non-governmental organization was not directly involved in the change in management. The main reason for this situation is that the understanding that the concrete activities of non-governmental organizations for change in management are viewed with suspicion in the management system has not changed in favor of non-governmental organizations.